2016
DOI: 10.1007/s10508-016-0692-8
|View full text |Cite
|
Sign up to set email alerts
|

Number of Sexual Partners and Relationship Status Are Associated With Unprotected Sex Across Emerging Adulthood

Abstract: Sex with multiple partners, consecutively or concurrently, is a risk factor for contracting sexually transmitted infections (STIs) as multiple partner–partner contacts present increased opportunity for transmission. It is unclear, however, if individuals who tend to have more partners also use protection less reliably than those with sexual histories of fewer partners. Longitudinal data can elucidate whether an individual shows a consistent pattern of sex with multiple partners. We used latent class growth ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 47 publications
8
43
1
1
Order By: Relevance
“…Similarly, males with more sexual partners may be less likely to know about a former partner’s pregnancy status. Alternatively, this may indicate more effective contraceptive behavior among those who have more partners, although this conflicts with previous research showing that those who initiate sexual activity earlier or have more sexual partners are less likely to use contraceptive methods at sexual debut and take longer to begin using contraception (Ashenhurst et al, 2017; Finer & Philbin, 2013). Further research is needed to understand how biological sex and contraceptive use may affect unintended pregnancy and/or knowledge about partner pregnancy among youth whose sexual start is similar to that of the Early/Atypical Initiators.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Similarly, males with more sexual partners may be less likely to know about a former partner’s pregnancy status. Alternatively, this may indicate more effective contraceptive behavior among those who have more partners, although this conflicts with previous research showing that those who initiate sexual activity earlier or have more sexual partners are less likely to use contraceptive methods at sexual debut and take longer to begin using contraception (Ashenhurst et al, 2017; Finer & Philbin, 2013). Further research is needed to understand how biological sex and contraceptive use may affect unintended pregnancy and/or knowledge about partner pregnancy among youth whose sexual start is similar to that of the Early/Atypical Initiators.…”
Section: Discussioncontrasting
confidence: 59%
“…The linkages between sexual initiation and subsequent sexual partnering, and their combined implications for sexual health, are not well understood because the majority of past research has focused on these two variables as independent predictors of sexual health outcomes (Ashenhurst, Wilhite, Harden, & Fromme, 2017; Harden, 2012; Kaestle, Halpern, Miller, & Ford, 2005). The studies that do consider both sexual initiation and partnering generally focus on the relationship between them, and do not go on to consider whether the particular combinations of sexual initiation and partnering patterns are differentially associated with later health (Harden, 2012; Lanza, Kugler, & Mathur, 2011; Moilanen, Crockett, Raffaelli, & Jones, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research using longitudinal methods (10 waves across six years) has identified three trajectories that capture emerging adults’ patterns of sexual partners across time: multiple partners, single partner, and rare partner (Ashenhurst, Wilhite, Harden, & Fromme, 2017). Individuals in the multiple-partner trajectory were up to 7.55 times more likely to report at least one instance of unprotected sex than individuals in the rare partner trajectory (Ashenhurst et al, 2017).…”
Section: Individual-level Factors Associated With Women’s Cur Utilizamentioning
confidence: 99%
“…Recent research using longitudinal methods (10 waves across six years) has identified three trajectories that capture emerging adults’ patterns of sexual partners across time: multiple partners, single partner, and rare partner (Ashenhurst, Wilhite, Harden, & Fromme, 2017). Individuals in the multiple-partner trajectory were up to 7.55 times more likely to report at least one instance of unprotected sex than individuals in the rare partner trajectory (Ashenhurst et al, 2017). Consistent with this research, and in support of the link between women’s number of sexual partners and CUR, Oncale and King (2001) found that 40% of women who tried to persuade a partner to have unprotected sex also reported five or more lifetime sexual partners.…”
Section: Individual-level Factors Associated With Women’s Cur Utilizamentioning
confidence: 99%
“…There is increasing evidence that risky health behaviors, which can include disordered eating, substance use, and sexual risk behaviors, tend to cluster together (Hingson & Zha, ; Mewton et al, ). Sexual risk behaviors that may cluster together include the number of sexual partners and unprotected sex (Ashenhurst, Wilhite, Harden, & Fromme, ), which are both associated with higher risk for sexually transmitted infections (STIs) (Kahn & Halpern, ; Pflieger, Cook, Niccolai, & Connell, ; Van Wagoner, Harbison, Drewry, Turnipseed, & Hook, ). One factor that may link risky behaviors such as disordered eating and risky sex is the personality trait of impulsivity (Culbert & Klump, ; Liang & Tseng, ).…”
Section: Introductionmentioning
confidence: 99%